Change in Neutrophil-to-Lymphocyte Ratio During Neoadjuvant Treatment Does Not Predict Pathological Response and Survival in Resectable Pancreatic Ductal Adenocarcinoma. Issue 6 (June 2022) - Strong, James S.; Vos, Elvira L.; Mcintyre, Caitlin A.; Chou, Joanne F.; Gonen, Mithat; Tang, Laura H.; Soares, Kevin C.; Balachandran, Vinod P.; Kingham, T. Peter; D'Angelica, Michael I.; Jarnagin, William R.; Drebin, Jeffrey; et al.
Background: Neutrophil-to-lymphocyte ratio (NLR) has been reported as prognostic in pancreatic ductal adenocarcinoma (PDAC). Data about NLR changes during neoadjuvant therapy (NAT) and its relationship with pathological tumor response and survival are lacking. Methods: Pancreatic ductal adenocarcinoma patients with NAT followed by resection between 2009 and 2015 were identified from a prospective database. Neutrophil-to-lymphocyte ratio was collected prior to NAT (baseline), on chemotherapy (prior to cycle 3), and prior to surgery. Baseline NLR, and changes in NLR between baseline and on chemotherapy (delta 1) and between baseline and surgery (delta 2) were compared with pathologic response (<90% and ≥90% defined as poor and good), overall (OS), and disease-free survival (DFS) using Wilcoxon rank-sum and Cox proportional hazard models. Results: Of 93 patients, 17% had good pathological response. Median (interquartile range) NLR at baseline, third cycle, and surgery were 2.7 (2.0-3.7), 2.5 (1.9-4.1), and 3.1 (2.1-5.3), respectively. Median change in NLR from baseline to third cycle was .06 ( P = .72), and .6 from baseline to surgery ( P < .01). Baseline NLR, delta 1, and delta 2 were not associated with pathological response, OS, or DFS. Discussion: Neutrophil-to-lymphocyte ratio increased after NAT, but a significant association between NLR and pathological response, OS, and DFS in resected PDAC patients was not observed.